2001
DOI: 10.1046/j.1464-410x.2001.02256.x
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological examination of both ipsilateral and contralateral testes with different obstructive models in prepubertal and adult rats

Abstract: Objective To determine the histopathological changes in both the ipsilateral and contralateral testes of prepubertal and adult male rats 60 days after creating different obstructive models. Material and methods Thirty-six prepubertal and 32 adult albino male rats were examined in three different obstructive models of the right testis. In group 1 the spermatic cord was ligated, in group 2 the ligation was between the caput epididymis and testis, and in group 3 the vas deferens was ligated. Sixty days after liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…The vacuolization of the seminiferous tubule may be as a result of toxigenic nature of residual cyanide in MFCP that could probably engender reduced fertility. This is similar to the vacuolization and degeneration of seminiferous tubule observed in rat due to obstruction or dysfunction of epididymis [29] [30] causing abnormal fluid reabsorption.…”
Section: Resultssupporting
confidence: 79%
“…The vacuolization of the seminiferous tubule may be as a result of toxigenic nature of residual cyanide in MFCP that could probably engender reduced fertility. This is similar to the vacuolization and degeneration of seminiferous tubule observed in rat due to obstruction or dysfunction of epididymis [29] [30] causing abnormal fluid reabsorption.…”
Section: Resultssupporting
confidence: 79%
“…On observation of paraffin sections within a relatively short period (18-60 days), some authors noted that ligation of spermatic vessels could produce varying degrees of injury of the operated testicle, but did not affect contralateral spermatogenesis [21][22][23]. However, based on the perfusion fixation and observation of the semithin sections, the present study found that from day 45 postoperatively, impaired spermatogenesis of contrallateral testes occurred when the SVCD testes showed atrophy, which might result in fertility due to mild disturbed spermatogenesis in postpuberty (45-180 days postoperative) or might result in subfertility or infertility owing to significantly impaired spermatogenesis (Sertoli cell only tubules) in middle age (360-540 days postoperative).…”
Section: Discussionmentioning
confidence: 99%
“…Care was provided in accordance with the guidelines published in the 1984 Guide for Care and Use of Laboratory Animals (National Institutes of Health, publication no. 85- 23,1985).…”
Section: Methodsmentioning
confidence: 99%
“…Experimental studies evaluating the influence of local trauma on the vas deferens with manipulations or extensive mobilizations demonstrated significant damage, which may contribute to infertility in animal models (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…The diminished fertility in unilateral testicular torsion might be attributed to the proven secondary effects of torsioned ipsilateral testis to the contralateral side. Most of these insults are observed to be time dependent and require long periods in order to exert biochemical and autoimmune effects (5)(6)(7). Additionally, some studies have suggested that a reflexive vasospasm preceded by sympathetic activation is another important factor resulting in contralateral testicular damage in unilateral spermatic cord torsion (8)(9)(10).…”
mentioning
confidence: 99%